Evolution and classification of figs (Ficus, Moraceae) and their close relatives (Castilleae) united by involucral bracts. (6th June 2020) - Clement, Wendy L; Bruun-Lund, Sam; Cohen, Alanna; Kjellberg, Finn; Weiblen, George D; Rønsted, Nina
Abstract: Figs and fig wasps are a classic example of an obligate pollination mutualism. Decades of work untangling the ecology and evolution of these organisms has simultaneously contributed to development of the fields of mutualism, coevolution and plant–insect interactions at large. With > 800 species, figs ( Ficus, Moraceae) are among some of the larger genera of angiosperms. Phylogenetic studies of Moraceae have supported the clade Castilleae as the sister lineage of Ficus . Compared to Ficus, Castilleae have many fewer species (60 species in 11 genera), suggesting changes in rates of diversification along these two branches. Relatively little is known about Castilleae compared to Ficus, and we argue that defining the clade comprising Ficus and Castilleae, hereafter Involucrata, focuses attention on opportunities for comparative studies of pollination mutualisms and diversification rates. In this study, we define Involucrata and propose a revised classification scheme that accounts for the phylogenetic reconstruction based on the most comprehensive sampling of this group to date. Moving forward, this classification will better guide and support evolutionary, ecological and comparative pollination biology studies of this group.